2020
DOI: 10.1002/pc.25667
|View full text |Cite
|
Sign up to set email alerts
|

Wear characteristics of glass‐polyester‐based hybrid composites: A parametric analysis using response surface method and fuzzy logic

Abstract: Marble dust generated during processing of the marble producing rocks is a major solid waste with a detrimental impact on environment. Analysis shows that this waste has constituents having compounds like SiO2, Al2O3, Fe2O3, CaO, MgO, etc., in different proportions. This paper explores on the possible use of waste marble dust as secondary filler in glass‐polyester composites and reports on its dry sliding wear characteristics. Such hybrid composites with unsaturated polyester as the matrix are fabricated by ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Therefore, the number of samples has to be reduced. As is well known, the response surface method [ 30 ] is an efficient tool for designing a process that operates effectively over a variety of conditions. In this study, three levels are selected for each process parameter.…”
Section: Material Manufacturing and Testingmentioning
confidence: 99%
“…Therefore, the number of samples has to be reduced. As is well known, the response surface method [ 30 ] is an efficient tool for designing a process that operates effectively over a variety of conditions. In this study, three levels are selected for each process parameter.…”
Section: Material Manufacturing and Testingmentioning
confidence: 99%
“…Composites with the highest marble dust content exhibited the lowest erosion rate regardless of the applied impingement angle and impact velocity. In their two literature reports, Nayak et al determined the sliding wear behavior of hybrid composites made of unsaturated polyester resin, E-glass fiber mat (10-layers, 40 wt %) and waste marble dust (0–16 wt %) [ 99 , 100 ]. The authors demonstrated that the highest sliding wear resistance was observed for the composites with maximal waste marble dust weight percentage (16 wt %).…”
Section: Industrial Waste Materialsmentioning
confidence: 99%
“…Based on the above results of the optimized Latin Hypercube test, the Design‐Expert software is used to select the response surface model (RSM) for the proxy model to optimize the crashworthiness of the composites beams with variable thickness. [ 32 ] Since the RSM has good robustness and a limited number of optimization parameters, the RSM is selected for polynomial fitting as Formula (). [ 7 ] y=f(),t1t2+ε, where y is the true response value, f is the approximate response polynomial, and ε is the response error.…”
Section: Multi‐objective Optimization Designmentioning
confidence: 99%
“…response surface model (RSM) for the proxy model to optimize the crashworthiness of the composites beams with variable thickness. [32] Since the RSM has good robustness and a limited number of optimization parameters, the RSM is selected for polynomial fitting as Formula ( 9). [7] y…”
Section: The Effects Of Thickness On the Crashworthinessmentioning
confidence: 99%